High Proportion of Adults With Type 2 Diabetes and Poor Glycated Hemoglobin Perceived That Their Diabetes Control Was Excellent - Mohammad Arif, Shahar; Ahmad Marzuki, Omar; Huai, Heng Loh (Elsevier B.V., 2019)
As is true for other chronic illnesses, perception of disease control is pivotal to patient empowerment in diabetes care. This study aimed to describe the perception of diabetes control by patients with poor glycated hemoglobin (A1C) levels so as to explore the relationship between perception and various sociodemographic and disease characteristics and to measure the patients’ knowledge, attitudes and practices in diabetes care. Methods: A cross-sectional study was made involving 276 patients with type 2 diabetes mellitus. After obtaining informed consent, their sociodemographics, medical histories and most recent available blood investigations were documented. Patients were asked about their perceptions of diabetes control—whether it was excellent, moderate or poor. A Malay-language knowledge, attitudes and practice questionnaire was administered to respondents. Analyses were descriptive and exploratory. Results: The median age of the subjects and the durations of diabetes were 56 (interquartile range, 48–62) years and 8 (interquartile range, 4–13) years, respectively. The median A1C level was 9.5% (interquartile range, 8.3%–11.4%). Despite having poor A1C levels, 28.4% of patients perceived that their diabetes control was excellent; 58.9% perceived it as moderate, and only 12.7% accurately perceived it as poor. A significant number of those with higher education had wrong perceptions, indicating that other factors, such as effective communication, need to be considered. The absence of an association between perception and duration of diabetes suggests that information given over the years did not contribute to patients’ understanding of disease control. Younger patients had better knowledge scores. Those with higher education levels had higher quartiles of knowledge and attitude but not practice scores. Conclusions: This study demonstrated discordance between perceived diabetes control and actual A1C levels, which may hinder effective diabetes care.